Trends in Biomathematics : Modeling, Optimization and Computational Problems : Selected works from the BIOMAT Consortium Lectures, Moscow 2017 /: Modeling, Optimization and Computational Problems : Selected works from the BIOMAT Consortium Lectures, Moscow 2017. ([2018]) - Unknown
No abstract available